Learning from and with the education movements in Greece and Brazil: knowledge, action and alternatives - Spyros Themelis (Educação & Realidade, 2018)
The insights shared in this paper are based on research conducted in Greece and Brazil It is centered around the exploration of activist knowledge as a distinct form of knowledge. In doing this, it discusses the role of reflection in acquiring critical consciousness as well as the unified and holistic character of activist knowledge. This unity entails the intertwining of action with reflection and action with theory. It shows how critique forms a key feature of activist knowledge and highlights some nuances, tensions and contradictions inherent in the knowledge production of this kind. The latter is shown to be underpinned by plural dialogical processes, which further challenge and enrich knowledge produced in social movements. The paper aims to feedback insights from theory into praxis and vice versa. To achieve its aims, it approaches learning as an ongoing part of the quest for meaning and the quest of meaning as an integral part of acting.